Human monocyte-derived dendritic cells as an in vitro alternative model cell to evaluate the immunotoxicity of 2, 4-Dinitrochlorobenzene. (15th September 2020) - Yao, Wu; Ding, Mingcui; Bao, Lei; Zhao, Youliang; Wang, Di; Li, Yiping; Qu, YaQian; Hao, Changfu
Highlights: Human monocyte-derived DC is an attractive cell to evaluate DNCB immunotoxicity. Blood center can provide stable leukocyte and greatly reduce the cost to obtain DC. Human monocyte-derived DCs had more comprehensive immune response capacity than THP-1. Abstract: Improvements in science and technology have led to the increasing threats of new chemicals to the public health. It is crucial to evaluate the toxicity, especially immunotoxicology. Dendritic cells (DCs) are believed to be more favorable choices in immunotoxicity evaluations. To obtain and evaluate the value of human monocyte-derived immature DCs (imDCs) in vitro applications in immunotoxicology, compared the results in vitro . DCs were obtained from enriched leukocytes of peripheral blood by using magnetic cell sorting and cytokine (rhGM-CSF + rhIL-4) co-induction. imDCs function in vitro and the surface antigens changes both in imDCs and THP-1 after 24 h of 2, 4-dinitrochlorobenzene (DNCB) exposure were determined. The results were compared with those of DNCB-induced rats. The feasibility of imDCs applications in immunotoxicology was evaluated. In vivo, the splenic nodules, lymphocytes, and CD103 + DC surface antigen expression were altered in the spleen of DNCB-induced rats. Moreover, DNCB exposure increased CD8 + T cell numbers both in peripheral blood and in the spleen of DNCB-induced rats. In vitro, DNCB exposure reduced the antigen uptake capacity and enhanced the T cell proliferative capacity of imDCs. The results are consistent with in vivo, but superior to that of the THP-1. Our results suggest that human monocyte-derived DCs may have potential applications as an attractive in vitro alternative cell model to evaluate the sensitization of DNCB.